Analysis of Design and Development of Website - Based Boarding Information System in Taman District - Muhammad Sukri (Journal of Engineering Science and Technology Management, 2022)
A boarding house is a place to provide lodging services or temporary residence consisting of several rooms, each room has several facilities offered or provided and also has a price that has been determined by the boarding house owner. Students take a long time and cost more to get information about boarding houses that they want. The problems faced by boarding house service owners are difficulties in marketing boarding house services and providing information to prospective boarding house residents regarding the availability of vacant rooms. Information systems have helped humans, one of which is website-based information technology. This research was conducted in the Tampan District, Pekanbaru City from April 25, 2021 to April 29, 2021. The population used in this study was 67 boarding houses spread across the Tampan District. The subject of this research is the owner of the boarding house. Collecting data using observation, interviews, documentation, and literature study. The method of testing carried out in this study is a direct test method, namely by black box testing. Based on the results obtained from a series of research processes regarding the Information System for Searching Boarding Houses in Tampan District, Web-Based. This website provides a platform for boarding house owners to promote and market their boarding houses and this website can also make it easier for people who want to book boarding rooms by registering on the website through the registration page.